UPACARA MAPEPEGAT NGABEN DI DESA OGOTION KECAMATAN MEPANGA KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Dewi, Ni Ketut Novira; Damayanti, Ni Luh Ayu Eka; ., Sugiarti (STAH Dharma Sentana Sulawesi Tengah, 2025)
Mapepegat is an important procession in Ngaben. Based on the Yama Tattwa text, appendix 10b, mapepegat is carried out after the ceremony has been completed in the hall before the body is taken to the grave, but in the Hindu community in Ogotion Village, the mapepegat ceremony is carried out twice, namely before the body is taken to the cemetery and after it has finished nganyut (throwing the ashes of the body into the sea). Seeing this difference is very important to research about the mapepegat Ngaben ceremony. The research objectives are: 1 to determine the form of implementation of the mapepegat Ngaben ceremony; 2 to find out the meaning of the Mapepegat Ngaben ceremony. The type of research is qualitative, determining informants using purposive sampling. Data collection methods are observation, interviews, documentation and literature study. Data analysis: data collection, data condensation, data presentation, conclusion drawing/verification. The theory used is the theory of structural functionalism and the theory of meaning, so that the research results obtained are: 1. The form of the mapepegat ngaben ceremony in Ogotion Village includes family and community, religious and spiritual, norms and values, adaptation and integration, religious goals and social motivation. 2 The meaning of the mapepegat Ngaben ceremony in Ogotion Village includes spiritual meaning, meaning of offerings and respect, meaning of social solidarity, meaning of cultural identity and meaning of spiritual communication.